Evolution Mount Rawdon—an integrated closure planning case study - Forbes, A; Ferrier, A (Mine Closure 2023: Proceedings of the 16th International Conference on Mine Closure, 2023)
Mine waste needs to be carefully managed throughout the life of a mining operation to achieve closure goals and minimize adverse environmental impacts. From a mine planners’ perspective, this means that waste dumps need to be designed to best achieve the final landform surface dictated by the site closure plan, inclusive of selective placement options. They then need to ensure that the material they’re mining is selectively placed to achieve that design. Unfortunately, a typical life of mine planning model will be built primarily to achieve ore or product tonnes, and would be limited to pits, haul road networks, ROM pads, and operational dumps without much consideration for closure. Integrating the mining and closure plans to include tailings storage facility embankments, waste rock storage facilities, sediment dams, bunds, and intermediate or final cover systems would provide visibility around whether the closure objectives can be achieved and improve the likelihood of achieving those closure objectives. Without an integrated mine closure plan, competitive use of materials and material deficits is likely to occur. Material deficits may result in unachievable or undesirable closure outcomes, as well as unexpected costs relating to rehandling, mining and rehabilitating a new ‘borrow’ area to make up the material shortfall. Evolution’s Mount Rawdon Operation brought together traditionally siloed mine planning, tailings, and environmental teams to deliver a Whole of Mine integrated mining and closure model (WOM model). This allowed them to test and analyse the material balance and landform development sequence for their Progressive Rehabilitation and Closure Planning (PRCP) and evaluate potential closure options to improve the likelihood of meeting closure objectives. The WOM model sequenced the remaining mining activities with the potential closure activities so they were shown in a single visualization. This became an effective tool to assess the viability of the selected closure option, quantify the overall rehabilitation material balance, and optimize material placement. The model quickly informed MRO that there would be a rehabilitation material deficit if they were to proceed with the closure option of covering the final landforms. Using this information, multiple scenarios were run to evaluate different borrow sources and cover placement options to achieve the potential closure option. The ‘final’ mining surface (the state of the operation at the completion of mining and processing activities) was output from the WOM model and used in the construction of a probabilistic GoldSim water quantity and quality model for the entire site. This was used to provide a range of probable water quality outcomes for the post-closure landform design. The WOM model was then integrated with the water modelling to verify catchment areas that report to each node in the GoldSim model and enabled MRO to evaluate the impact of the selected material placement strategy on the water modelling. The WOM model identified opportunities and risks for both mining operations and closure activities and is an outstanding example of designing for closure and implementing integrated planning.